Effects of milling atmosphere and increasing sintering temperature on the magnetic properties of nanocrystalline Ni0.36Zn0.64Fe2O4 - Hajalilou, Abdollah (Hindawi Publishing Corporation, 2015)
Nanocrystalline Ni0.36Zn0.64Fe2O4 was synthesized by milling a powder mixture of Zn, NiO, and Fe2O3 in a high-energy ball mill for 30 h under three different atmospheres of air, argon, and oxygen. After sintering the 30 h milled samples at 500°C, the XRD patterns suggested the formation of a single phase of Ni-Zn ferrite. The XRD results indicated the average crystallite sizes to be 15, 14, and 16 nm, respectively, for the 30 h milled samples in air, argon, and oxygen atmospheres sintered at 500°C. From the FeSEM micrographs, the average grain sizes of the mentioned samples were 83, 75, and 105 nm, respectively, which grew to 284, 243, and 302 nm after sintering to 900°C. A density of all the samples increased while a porosity decreased by elevating sintering temperature. The parallel evolution of changes in magnetic properties, due to microstructural variations with changes in the milling atmosphere and sintering temperature in the rage of 500–900°C with 100°C increments, is also studied in this work.